Transactions on large-scale data- and knowledge-centered systems III special issue on data and knowledge management in grid and P2P systems - Hameurlain, Abdelkader; Küng, Josef; Wagner, Roland (Lecture Notes in Computer Science, 2011)
The LNCS journal Transactions on Large-Scale Data- and Knowledge-Centered Systems focuses on data management, knowledge discovery, and knowledge processing, which are core and hot topics in computer science. Since the 1990s, the Internet has become the main driving force behind application development in all domains. An increase in the demand for resource sharing across different sites connected through networks has led to an evolution of data- and knowledge-management systems from centralized systems to decentralized systems enabling large-scale distributed applications providing high scalability. Current decentralized systems still focus on data and knowledge as their main resource. Feasibility of these systems relies basically on P2P (peer-to-peer) techniques and the support of agent systems with scaling and decentralized control. Synergy between Grids, P2P systems, and agent technologies is the key to data- and knowledge-centered systems in large-scale environments. This, the third issue of Transactions on Large-Scale Data- and Knowledge-Centered Systems, contains two kinds of papers: Firstly, a selection of the best papers from the third International Conference on Data Management in Grid and Peer-to-Peer Systems, Globe 2010, and secondly, a selection of 6 papers from the 18 papers submitted in response to the call for papers for this issue. The topics covered by this special issue include replication, the semantic web, information retrieval, data storage, source selection, and large-scale distributed applications.